From Contract of Work to Licensing Regime: Balancing State Sovereignty and Legal Certainty in Indonesia’s Mining Law Transformation - Mohamad Syah Indra Aman; Richard C. Adam (Greenation International Journal of Law and Social Sciences, 2026)
The transformation of Indonesia’s mining legal framework from the contract of work regime to the licensing regime represents a significant restructuring of the relationship between the state and investors in the governance of natural resources. While this shift reflects an effort to strengthen state sovereignty and enhance regulatory control over strategic resources, it also raises complex questions regarding the evolving nature of legal certainty in investment activities. This study aims to critically examine the comparative characteristics of both regimes and their implications for legal certainty within Indonesia’s mining sector. The research employs a normative juridical method supported by statutory, conceptual, and comparative approaches. The findings indicate that the relationship between contractual stability and administrative flexibility is not strictly dichotomous, but rather reflects a dynamic tension shaped by regulatory design, institutional practice, and governance objectives. Although the licensing regime increases state discretion in resource management, its impact on legal certainty is contingent upon regulatory consistency and institutional coherence, rather than the regime itself. This study concludes that the transformation of mining law should not be interpreted as a linear decline or improvement in legal certainty, but as a complex reconfiguration of legal governance that requires a more balanced approach between state authority, investor protection, and sustainable resource management.